Penggunaan Kata Sapaan Pada Akun Twitter Ganjar Pranowo @Ganjarpranowo Dan Implementasinya Dalam Pembelajaran Bahasa Indonesia Kelas X SMA/MA - Aprilia, Dwi, Drs. Agus Budi Wahyudi, M.Hum (2016)
Greeting interaction patterns can occur through intermediary media such as telephone, SMS, and social media such as twitter. One of the officials who use twitter social media to interact with people is Ganjar Pranowo.This study aimed to describe the shape of the word greetings on his twitter account @ganjarpranowo, variations of the word greetings on his twitter account @ganjarpranowo, and implementation of the use of the word greeting in Indonesian learning class X SMA / MA. The method used in this research is qualitative method. The data in this study is a sentence containing the word greetings. Sources of data in this study is the twitter account @ganjarpranowo. The data collection technique used is the technique and techniques refer to note. Data already classified and then analyzed using the methods agih. Based on the analysis, it is known that there are 39 forms of use and 18 variations of said greeting words @ganjarpranowo greeting on his twitter account. The breakdown is 2 greeting pronoun persona (Kamu and Anda), 24 greeting kinship (Bapak, Pak, Mas, Kang, Mbak, Eyang, Pakdhe, Paklik, Om, Pak Gan, Pak Ganjar, Pak Bupati, Pak Menteri, Pak Ketua, Pak Wakil, Pak Bos, Pak Ganteng, Bu Dokter, Bu Bupati, Mas Ganjar, Mas Gubernur, Mas Gub, Mas Twit), 3 greeting term Java (Ndoro, Den, and Jeng) 2 greeting titles and positions Profesor andGubernur), 2 greeting other pronouns (Bung and Tuan), 1 greeting proper name (GP), 3 greetings from English (Mr, Bro, and Bos) the results of the data analysis will be implemented in the negotiating text learning class X SMA/MA. Keywords: greeting words, greeting word forms, variations of the word greeting.